The Effect of Probable Alignment of America in Trump Era (2016- 2020) in Fighting against Daish on the Foreign Policy of Arabia : Trump and Russia - Ghobady, Yousef (Acta Universitatis Danubius. Relationes Internationales, 2021)
Abstract Since World War II up to now, the relation between Russia and America has been among the most important international problems and it has affected the international policy and even the relations of other governments more than any other relation. The major part of this significance goes back to its systemic outcomes for the global system and political and security problems. Because, the effects of the relations of these two countries on the international system and its different problems in different domains can help to the formation of crises or their ending. Also, over time, one of the most complicated political and security challenges in the region is Syria crisis. On the other hand, political changes of Syria have provided an arena for the composition of regional and trans-regional powers. Each one of these powers has applied different procedures regarding Syria that America and Russia’ functions are of significant importance as two global superpowers. The aim of this paper is evaluating the effect of probable alignment of America and Russia in Trump era (2016-2020) in fighting against Daish on the foreign policy of Arabia. From many analysts’ point of view, foreign policy of America has been so ambiguous versus civil war in Syria. We concluded that we could predict the future relation of America and Russia in Trump era based on Trump’s viewpoint. Trump declared that this country’s policy in Syria should have been concentrated on fighting against Daish terrorist group and not Assad’s regime.